Linear Random Early Detection for Congestion Control at the Router Buffer - Abu-Shareha, Ahmad; Al-Kasasbeh, Basil; Shambour, Qusai Y.; Abualhaj, Mosleh M.; Alsharaiah, Mohmmad Abdalla; Al-Khatib, Sumaya N. (Informatica, 2022)
Active Queue Management (AQM) methods control the router's buffer to maintain high network performance and control congestion at the router buffer. Random Early Detection (RED) method is the most well-known and the most utilized AQM. RED suffers from a high dropping rate, which motivates the later AQM methods to use more complex processes, which reach the limits of using fuzzy systems as a processing technique. Yet, high computational cost affects the performance at the router specifically and the network as a whole, with so-called processing delay. In this paper, a linear version of RED (LRED) is presented to reduce the computational cost of the original RED and maintain the network performance in terms of throughput, delay, dropping, and loss. LRED is built based on two distinctive features, simplifying the congestion indicator calculation and reducing the operations in calculating the dropping probability. The experimental results showed that the proposed method reduces the delay and the processing time while maintaining the throughput and loss of the RED method.